The Cause and Effect of Cultural Dynamics on the Relationship between Media Framing and the Perception of Obesity among 35-55 years University Female Academic Staff in Nairobi County, Kenya - Kahiga, Naomi; Mberia, Hellen; Wa Ngula, Kyalo (International Journal of Communication and Public Relation, 2021)
Purpose: To assess the moderating influence of cultural dynamics on the relationship between media framing and the perception of obesity among middle-aged women in Nairobi County, Kenya. Methodology: This study applied the one-group pretest-posttest experimental design. In the one-group pretest-posttest experimental design all study participants provided with the same treatment and assessment. The researcher therefore, collected data using the pre-and posttest questionnaires. The treatment administered was a television program titled Slimpossible, which showcased middle-aged Kenyan women suffering from the stigma of obesity who were participating in a competition to lose their weight. The multi-stage cluster sampling technique was applied in this study. Out of the target population of 1848 participants, the study sample was 317 academic female staff found in three public universities in Nairobi County, Kenya. In this research study, the analysis applied descriptive statistics and the inferential analysis tools such as the Factor analysis (The Keiser-Meyer -Olkin (KMO) test), Pearson's correlation coefficient and regression analysis (logical regression). Findings: The study sought to assess the moderating influence of cultural dynamics on the relationship between media framing and the perception of obesity among middle-aged women in Nairobi County, Kenya. Therefore, the finding also brought about interactions between cultural dynamics and the independent media frames in connection to the perception of obesity. It was concluded that the perception of obesity from the African culture and Western culture was different. The respondents had positive outlook on middle-aged obese women opposed to the dictates of Western culture. Unique contribution to theory, practice and policy: In terms of contribution to theory, this study emanated from the cross-cultural communication theory. The theory recognizes the value of culture and how it relates to people's perception on obesity. Hurn and Tomalin (2013) opined that some of the most strategic researchers in the field of cross-cultural communication include Edward Hall, Mildred Hall and Geert Hofstede in the 1950s.